The Lark Farm or How to Tell the Armenian Genocide: From the Novel (2004) by Antonia Arslan to the Cinematographic Realization (2007) of the Taviani Brothers - Zidarič, Walter (Translation Studies: Theory and Practice, 2023)
The Lark Farm (2004) by Antonia Arslan, an Italian author of Armenian origin, was both a bestseller and a highly valued literary piece for Italians. Retracing the events of 1915, in Anatolia, the novel tells the story of the writer’s family, between Italy and her native country, at a fateful moment in history. The uncle in the romantic fiction was in fact the grandfather of the author-narrator, hence the work of memory recovery of the history of his family on the part of Arslan, which leads to the denunciation of the Armenian genocide. Following the phenomenal success of the book, the filmmakers Paolo and Vittorio Taviani also looked into the question of the Armenian genocide and produced their cinematographic work in 2007. While remaining very close to the romantic fiction of Arslan, they have, however, introduced several new elements in the filmic narration by using the melodramatic model as a watermark of their aesthetic discourse.